Cui narro haec ? Augustine and his Manichaean audience: A re-reading of the first three books of the Confessions - Kotzé, Annemaré (HTS teologiese studies, 2013)
The issue of intended audience in the first three books of Augustine’s Confessions is investigated in light of the presence of terms and phrases that may have had special connotations for potential Manichaean readers. This is done against the background of definitions of protreptic and paraenetic, which typically revolve around audience location and communicative purpose. Although it has become commonplace to refer to the Confessions as a protreptic the work displays a number of characteristics more in line with current mainstream definitions of paraenetic, amongst other things, by assuming the stance of addressing insiders in agreement with the author’s world view. It is argued that the type of reader most receptive to the insider stance and allusion to the Old Testament on the one hand and to the Manichaean material on the other, would be a Manichaean apostate recently converted to Catholic Christianity.